Ambition Reflected in Agatha Christie's Endless Night Novel (1967): A Psychoanalytic Criticism - Parwanti, Tri, Titis Setyabudi, S.S. M.Hum (2016)
The study is purposed to show ambition of Michael Rogers, the main character in Endless night novel. Object of the study of this research is the novel. This research analyzes the ambition of Michael Rogers that deals with id, ego, and superego using psychoanalytic criticism. This study is qualitative research using Agatha Christie's Endless Night novel (1967) as the object. There are two kinds of data source: primary and secondary data sources. The primary data source is the novel of Endless Night and secondary data sources are reference books. The method of collecting data is note taking by reading the novel and taking notes for important things for both primary and secondary data. Based on the psychoanalytic analysis, the novel tells that the major character, Michael Rogers has ambition to get everything what he wants with the wrong ways. Keywords: ambition, Endless Night, psychoanalytic criticism